PENGARUH RETURN ON ASSETS (ROA) DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Aini Fitriani; Ade Fauji; Aria Cendana Kusuma (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
This study aims to examine the effect of Return On Assets (ROA) and Dividend Policy on Company Value in financial companies in the banking sub-sector listed on the Indonesia Stock Exchange for the 2016-2020 period.  This study used a sample of 11 companies.  The sampling technique used is purposive sampling.  The results showed that, partially, Return On Assets (ROA) had an effect on company value, and Dividend Policy had no effect on Company Value.  However, simultaneously, Return On Assets (ROA) and Dividend Policy have an effect on Company Value